Interpreting marine controlled source electromagnetic field behaviour with streamlines - Pethick, A.; Harris, Brett (Elsevier, 2013)
Streamlines represent particle motion within a vector field as a single line structure and have been used in many areas of geophysics. We extend the concept of streamlines to interactive three dimensional representations of the coupled vector fields generated during marine controlled source electromagnetic surveys. These vector fields have measurable amplitudes throughout many hundreds of cubic kilometres. Electromagnetic streamline representation makes electromagnetic interactions within complex geo-electrical setting comprehensible. We develop an interface to rapidly compute and interactively visualise the electric and magnetic fields as streamlines for 3D marine controlled source electromagnetic surveys. Several examples highlighting how interactive use has value in marine controlled source electromagnetic survey design, interpretation and teaching are provided. The first videos of electric, magnetic and Poynting vector field streamlines are provided along with the first published example of the airwave represented as streamlines. We demonstrate that the electric field airwave is a circulating vortex moving down and out from the air–water interface towards the ocean floor. The use of interactive streamlines is not limited to marine controlled source electromagnetic methods. Streamlines provides a high level visualisation tool for interpreting the electric and magnetic field behaviour generated by a wide range of electromagnetic survey configurations for complex 3D geo-electrical settings.